Changes in undergraduate medical education practices during COVID-19 pandemic - Mukund Sable; Saurav Sarkar; Vinaykumar Hallur; Priyadarshini Mishra (Wolters Kluwer Medknow Publications, 2021)
Introduction: The countrywide lockdown in response to COVID-19 pandemic necessitated a shift from conventional teaching to online teaching. This study aimed to find the issues and challenges faced by medical teachers on the virtual platforms of teaching during lockdown. Material and Methods: A cross-sectional survey was conducted among the medical teachers of a tertiary care hospital between august to october 2020. A google form with study questionnaire was circulated among participants. Results: Online live lectures were major mode of online teaching. 36.5% of teachers felt that they were successful and only 19.2% felt, they were unsuccessful in engaging most of the students. Discrepancies between efforts and outcome (20.54%), absence of definite guidelines (20.54%), unwanted disturbances (19.17%), lack of technical expertise (19.17%), absence of uniform format (10.95%), and lack of knowledge (6.84%) were the challenges faced. A change in the content of slides (52.8%), increased use of videos, charts, and figures (41.5%), changes in lesson plan (32.1%), including assessments after each class (28.3%) and division of content into sub-topics for better understanding and easy upload (22.6%) were the modifications made by faculty for online teaching. Around half of the faculty members disagreed that teaching can be conducted online postlockdown. Conclusion: The pandemic is a situation that should encourage all medical educators to be trained and adapt to online teaching methodologies.